System Characteristics (Docentes 2.0 Journal, 2016)
When man thinks of images, he can attract a lot of information to the mind at the same time, which is why people who use the visual representation system have a much easier time absorbing large amounts of information quickly. Visualize help, to establish relationships between different ideas and concepts. When a student has trouble relating concepts, it is often due to the fact that he is processing the information in an auditory or kinesthetic way.
Keywords: System; Characteristics